2012
DOI: 10.1002/lary.22505
|View full text |Cite
|
Sign up to set email alerts
|

Safety analysis of percutaneous dilational tracheostomies with bronchoscopy in the obese patient

Abstract: PDT can be performed safely in obese patients. There were no statistically significant differences in measured variables found between the two study groups. This study supports the use of intensive care unit bedside PDT in the obese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 6 publications
2
28
2
Order By: Relevance
“…As described previously, 10 we could not detect an elevated complication rate assigned to the procedure of percutaneous tracheotomy in our cohort of obese subjects. Because we did not detect severe complications, such as cannula dislocation, bleeding, or pneumothorax due to PDT, we believe that early PDT probably does not contribute to mortality in this group of subjects.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…As described previously, 10 we could not detect an elevated complication rate assigned to the procedure of percutaneous tracheotomy in our cohort of obese subjects. Because we did not detect severe complications, such as cannula dislocation, bleeding, or pneumothorax due to PDT, we believe that early PDT probably does not contribute to mortality in this group of subjects.…”
Section: Discussionsupporting
confidence: 58%
“…9 Obesity was initially deemed to be a relative contraindication for PDT, but several studies showed that this procedure could be safely performed in obese subjects. [9][10][11][12] A study by Pelosi et al 13 in sedated, paralyzed, morbidly obese subjects undergoing general anesthesia for abdominal surgery found during the postoperative period a reduction of compliance and increase of resistance of the respiratory system, reduced functional residual capacity, increased work to inflate lungs and chest wall, and reduced pulmonary oxygenation index. Extremely obese patients have longer durations of mechanical ventilation and prolonged stays in the ICU compared with normal-weight patients.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies reported that SDT was equally effective and safe in both obese and non-obese patients. 17,18,21 However, it should be acknowledged that so far, no RCT compared the SDT with GWDF or other PDT techniques in hypoxaemic or obese patients; moreover, in our meta-analysis, we found no difference in the incidence of oxygen desaturation.…”
Section: Discussioncontrasting
confidence: 51%
“…Excluding 1006 non-pertinent titles or abstracts, we retrieved in complete form and assessed according to the selection criteria 34 studies. After excluding 10 articles that were not randomised, [13][14][15][16][17][18][19][20][21][22] twelve articles that had another PDT as comparator [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and seven that were reviews, 1,2,7,35-38 we finally identified five eligible RCTs, [8][9][10]39,40 which were included in the final analysis. …”
Section: Search Resultsmentioning
confidence: 99%
“…However, serious adverse events are still reported [13,14]. The high rate of difficulty in placement and malposition [7,15] up to 20 %, is the source of major intraprocedural events like hemorrhage or airway complications. In order to increase the ease and the safety of this invasive procedure, PDT has been improved over the time.…”
mentioning
confidence: 99%